2017
DOI: 10.1080/02713683.2017.1358372
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Flicker-Induced Retinal Vessel Vasodilatation and Plasma Biomarkers of Endothelial Dysfunction in Hypertensive Patients

Abstract: Our results indicate that DVA directly reflects the actual metabolic status of the retinal endothelium. DVA might be used as an early noninvasive screening tool to detect vascular dysregulation and pan-endothelial dysfunction in patients with HT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Sörensen et al (2016) demonstrated reduced FID in patients with prediabetes compared to healthy individuals with further impairments in patients with manifest type 2 diabetes (Sörensen et al, 2016). Impaired FID has also been associated with hypertension (Machalinska et al, 2018), hypercholesterolemia (Nagele et al, 2018a), obesity (Kotliar et al, 2011) and higher age (Kneser et al, 2009). With respect to static retinal vessel diameters, narrower arterioles, wider venules and a resulting lower arterio-venous ratio (AVR) have been associated with incidence hypertension (Wang et al, 2003; Wong et al, 2004; Ikram et al, 2006b), stroke (Ikram et al, 2006a; McGeechan et al, 2009) and a higher CV morbidity and mortality (Wang et al, 2007; Seidelmann et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Sörensen et al (2016) demonstrated reduced FID in patients with prediabetes compared to healthy individuals with further impairments in patients with manifest type 2 diabetes (Sörensen et al, 2016). Impaired FID has also been associated with hypertension (Machalinska et al, 2018), hypercholesterolemia (Nagele et al, 2018a), obesity (Kotliar et al, 2011) and higher age (Kneser et al, 2009). With respect to static retinal vessel diameters, narrower arterioles, wider venules and a resulting lower arterio-venous ratio (AVR) have been associated with incidence hypertension (Wang et al, 2003; Wong et al, 2004; Ikram et al, 2006b), stroke (Ikram et al, 2006a; McGeechan et al, 2009) and a higher CV morbidity and mortality (Wang et al, 2007; Seidelmann et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, there was no link between SDD and retinal vessel diameters or reactivity. These parameters indirectly indicate the function of the vascular endothelium, and their disturbance in arterial hypertension, atherosclerosis, and CAD has been previously demonstrated [98][99][100][101]. Interestingly, Rabiolo et al observed a reduced dilation response of the retinal arteries in eyes with SDD [22].…”
Section: Discussionmentioning
confidence: 89%
“…Similarly, to exclude factors that could distort the test results, patients were advised to refrain from drinking coffee or smoking cigarettes for at least 5 h before the examination. During the static vessel analysis (SVA), 30-degree retinal photographs of each subject were taken with the FF450 plus fundus camera (Zeiss AG, Jena, Germany), as previously described [14,28]. The images were further analysed using VISUALIS and VesselMap software (IMEDOS Systems, Ltd., Jena, Germany).…”
Section: Retinal Vessel Analysismentioning
confidence: 99%